USM OPENS OPERATIONS ROOM TO MONITOR WORSENING HAZE SITUATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 October 2015 In view of the worsening haze situation, Universiti Sains Malaysia (USM) has advised its students and the campus community not to hold any outdoor activities at all its campuses in Penang, Nibong Tebal, Bertam and Kubang Kerian, Kelantan.